Proposed improvement plan with Lean manufacturing to increase productivity in a SME in the textile sector in Peru - Dueñas Añazco, Luis Brian (2023)
In Peru, the textile industry is the third activity with the highest contribution to manufacturing GDP. However, most companies suffer from a lack of production planning, organizational culture and training. This research has focused on the development of a proposed improvement model, combining Lean Manufacturing and Systematic Layout Planning tools to solve the main problems that arise in this type of companies. Which is evaluated through a simulation in the Software Arena for validation, where a 39.76% decrease in transfer time, a 15.11% reduction in cycle time and a 17.99% increase in productivity was obtained.